Basal forebrain thermoregulatory mechanism modulates auto-regulated sleep - Mallick, Hruda N.; Kumar, Velayudhan M. (Frontiers in Neurology, 2012)
Regulation of body temperature and sleep are two physiological mechanisms that are vital for our survival. Interestingly neural structures implicated in both these functions are common. These areas include the medial preoptic area, the lateral preoptic area, the ventrolateral preoptic area, the median preoptic nucleus and the medial septum, which form part of the basal forebrain. When given a choice, rats prefer to stay at an ambient temperature of 270C, though the maximum sleep was observed when they were placed at 300C. Ambient temperature around 270C should be considered as the thermoneutral temperature for rats in all sleep studies. At this temperature the diurnal oscillations of sleep and body temperature are properly expressed. The warm sensitive neurons of the preoptic area mediate the increase in sleep at 300C. Promotion of sleep during the rise in ambient temperature from 270C to 300C, serve a thermoregulatory function. Autonomous thermoregulatory changes in core body temperature and skin temperature could act as an input signal to modulate neuronal activity in sleep-promoting brain areas. The studies presented here show that the neurons of the basal forebrain play a key role in regulating sleep. Basal forebrain thermoregulatory system is a part of the global homeostatic sleep regulatory mechanism, which is auto-regulated.